The spectrum of ammonia near 0.793 μm. (October 2021) - Zobov, N.F.; Bertin, T.; Vander Auwera, J.; Civiš, S.; Knížek, A.; Ferus, M.; Ovsyannikov, Roman I.; Makhnev, Vladimir Yu.; Tennyson, Jonathan; Polyansky, Oleg L.
Highlights: Two ammonia spectra are recorded in the 11000 – 14500 cm-1 region. 278 lines are assigned using combination differences and variational nuclear motion calculations. 119 new energy levels belonging to 16 vibrational states are determined. Abstract: Two sets of NH 3 absorption spectra covering the 0.793  μ m region are recorded using two Bruker IFS 125 HR Fourier transform spectrometers. Three unapodized absorption spectra are recorded in Brussels over the range 11000 − 14500 cm − 1 and the positions and intensities of 1114 ammonia lines observed in the 12491 − 12810 cm − 1 region are measured using a multi-spectrum least squares fitting algorithm. 367 additional lines are identified in an ammonia absorption spectrum recorded in two steps at the J. Heyrovsky Institute of Physical Chemistry in Prague, using two different interference filters covering the 12000 − 12500 and 12400 − 13000 cm − 1 ranges. The 1481 measured ammonia lines are analyzed using an empirical line list computed using variational nuclear motion calculations and ground state combination differences. Transitions are assigned to vibrational states with 4 ν N H stretching excitation ( v 1 + v 3 = 4 ) . 278 out of the 1481 measured lines are assigned to 300 transitions and 119 upper state energy levels are derived from the frequencies of the assigned transitions.